2013
DOI: 10.1038/nphys2761
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt transition in the structural formation of interconnected networks

Abstract: Our world is linked by a complex mesh of networks through which information, people and goods flow. These networks are interdependent on each other, and present structural and dynamical features 1-6 different from those observed in isolated networks 7-9 . Although examples of such dissimilar properties are becoming more abundant-such as in diffusion, robustness and competition-it is not yet clear where these differences are rooted. Here we show that the process of building independent networks into an intercon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
344
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(371 citation statements)
references
References 30 publications
(38 reference statements)
14
344
0
10
Order By: Relevance
“…Similarly, in biological systems basic constituents such as proteins can have physical, co-localization, genetic or many other types of interactions. Recently, it has been shown that retaining such multi-dimensional information 7 and modelling the structure of interdependent and multilayer systems respectively through interdependent 8 and multilayer networks [9][10][11][12] reveals new nontrivial structural properties [13][14][15][16][17][18][19][20] and relevant emergent physical phenomena [21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…Similarly, in biological systems basic constituents such as proteins can have physical, co-localization, genetic or many other types of interactions. Recently, it has been shown that retaining such multi-dimensional information 7 and modelling the structure of interdependent and multilayer systems respectively through interdependent 8 and multilayer networks [9][10][11][12] reveals new nontrivial structural properties [13][14][15][16][17][18][19][20] and relevant emergent physical phenomena [21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…Note that the change between λ 2 and either λ 1 2 or λ 2 2 being maximal is related to the transitions pointed out in Ref. [3,16]. This behavior is shown in Fig.…”
Section: Multi-layer Aggregationmentioning
confidence: 58%
“…For continuity, at p * ,μ 3 = mp must hold, since mp is always an eigenvalue of the supra-Laplacian. p = p * is the point at which the structural transition described in [7,14] occurs, as already noted by Darabi Sahneh et al [15]. Each eigenvalue up toμ n will follow the same pattern, following the lineμ i = mp and departing from it to approach its boundμ (a) i when it hits the next eigenvalueμ i+1 = mp (see Fig.…”
Section: Characterization Of Multiple Topological Scales In Multiplexmentioning
confidence: 81%
“…So far, theoretical studies have pointed out that this is indeed the case [4][5][6]. Moreover, as recently shown [7,8], multiplex networks might show different structural phases. Namely, under some conditions, the multiplex system might behave as one interconnected system, while in other conditions, the layers can become effectively disconnected and behave as if they were isolated [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation